A trigger mechanism of herbicides to phytoplankton blooms: From the standpoint of hormesis involving cytochrome b559, reactive oxygen species and nitric oxide. (15th April 2020) - Zhang, Yueheng; Calabrese, Edward J.; Zhang, Junyi; Gao, Dan; Qin, Mengnan; Lin, Zhifen
Abstract: The cause of phytoplankton blooms has been extensively discussed and largely attributed to favorable external conditions such as nitrogen/phosphorus resources, pH and temperature. Here from the standpoint of hormesis response, we propose that phytoplankton blooms are initiated by stimulatory effects of low concentrations of herbicides as environmental contaminants spread over estuaries and lakes. The experimental results revealed general stimulations by herbicides on Microcystis aeruginosa and Selenastrum capricornutum, with the maximum stimulation in the 30–60% range, depending on the agent and experiment. In parallel with enhancing stimulation, the ratio of HP (high-potential) form to LP (low-potential) form of cytochrome b 559 (RHL) was observed decreasing, while intracellular reactive oxygen species (ROS) were observed increasing. We propose that the ROS originated from the thermodynamic transformation of cytochrome b 559, enhancing the stimulatory response. Furthermore, the results also proved that thermodynamic states of cytochrome b 559 could be modulated by nitric oxide, thus affecting cellular equilibrium of oxidative stress (OS) and correspondingly causing the inhibitory effect of higher concentrations of herbicides on phytoplankton. This suggests that hormesis substantially derives from equilibrium shifting of OS. Moreover, it is reasonable to infer that phytoplankton blooms would be motivated by herbicides or other environmental pollutants. This study provides a new thought into global phytoplankton blooms from a contaminant perspective. Graphical abstract: Image 1 Highlights: The experimental results revealed hormesis effects by herbicides on Microcystis aeruginosa and Selenastrum capricornutum . Cytochrome b 559 played a vital role in alleviating photoinhibition caused by herbicides. Hormesis response substantially derived from equilibrium shifting of oxidative stress. It is proposed that low concentrations of water pollutants are supportive factors in the formation of phytoplankton blooms.